2020
DOI: 10.1021/acs.langmuir.0c02266
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Free Fatty Acids on Lipid Membrane–Nisin Interaction

Abstract: The influence of free fatty acids (FFAs) on the nisin–membrane interaction was investigated through micro-DSC and fluorescence spectroscopy. A simple but informative model membrane was prepared (5.7 DMPC:3.8 DPPS:0.5 DOPC molar ratio) by considering the presence of different phospholipid headgroups in charge and size and different phospholipid tails in length and unsaturation level, allowing the discrimination of the combined interaction of nisin and FFAs with the single phospholipid constituents. The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Biological membranes comprise lipid bilayers, which not only act as an insulating film to physically separate cells from the external environment but also play important roles in the selective transportation of small molecules and ions as well as cell–cell communication across membranes. Since the physical properties of biological membranes largely depend on the structure, composition, and distribution of lipids in bilayers, , a considerable number of studies have been conducted on model lipid bilayers largely based on physicochemical methodologies and have led to elucidation of the functions of lipid structural components, such as an ionic head group, hydrophobic chains, and their linking moiety. Particularly, the temperature-dependent behavior of the acyl and other hydrocarbon chains has been investigated from the aspect of chain length, degree of unsaturation, and methyl substitution. Except for the pioneering studies by Seelig’s group and several groups, chain packing and melting of model bilayers generally focus on the intermolecular interactions of the entire alkyl chains. The local mobility of the chain segment is often overlooked for the following reasons: (1) the hydrocarbon chains have a simple structure and flexible nature, making segmental analysis along the depth of a bilayer difficult, particularly in the gel (L β ) or ripple (P β ) phase, and (2) the hydrocarbon chains of lipids largely comprise simple repeating methylene units, which hampers the observation of a specific segment using spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Biological membranes comprise lipid bilayers, which not only act as an insulating film to physically separate cells from the external environment but also play important roles in the selective transportation of small molecules and ions as well as cell–cell communication across membranes. Since the physical properties of biological membranes largely depend on the structure, composition, and distribution of lipids in bilayers, , a considerable number of studies have been conducted on model lipid bilayers largely based on physicochemical methodologies and have led to elucidation of the functions of lipid structural components, such as an ionic head group, hydrophobic chains, and their linking moiety. Particularly, the temperature-dependent behavior of the acyl and other hydrocarbon chains has been investigated from the aspect of chain length, degree of unsaturation, and methyl substitution. Except for the pioneering studies by Seelig’s group and several groups, chain packing and melting of model bilayers generally focus on the intermolecular interactions of the entire alkyl chains. The local mobility of the chain segment is often overlooked for the following reasons: (1) the hydrocarbon chains have a simple structure and flexible nature, making segmental analysis along the depth of a bilayer difficult, particularly in the gel (L β ) or ripple (P β ) phase, and (2) the hydrocarbon chains of lipids largely comprise simple repeating methylene units, which hampers the observation of a specific segment using spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Free fatty acids (FFAs) are essential components of biological membranes that are important for their functioning: they increase the membrane fluidity, serve as energy supply and a source of structural components, and participate in a number of biological processesfrom the cell signaling up to the fusion of lipid vesicles and cells. FFAs are continuously being produced and degraded, providing so a regulatory function in the cell. Under some pathological conditions, their substantial increase is observed, which may serve as a protective mechanism …”
Section: Introductionmentioning
confidence: 99%
“…Cell membrane thermodynamic stability depends on several factors such as size, lipid composition, phospholipid headgroup and tails, unsaturation level, etc. These aspects has been extensively studied and reported in recent works [24][25][26] starting from simple systems up to fifteen component complex membranes. This systematic dissection of the thermodynamic determinants dictating the cell membrane stability and the assessment of an interaction hierarchy allowed to downgrade the complexity of the system and to design a simple but informative model lipid membrane that highly reproduced the thermodynamic behaviour exhibited by real cell membranes 24 .…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…23 Nevertheless, the molecular aspects of the stilbenoid-membrane interaction are still missing in the literature and deserve to be addressed to directly assess such an interaction and to highlight peculiarities of each compound. Indeed, previous calorimetric and spectroscopic studies [24][25][26][27][28] revealed that cell membranes may be severely affected by external agents, but the interaction effects are usually peculiar and strongly dependent on the stereochemistry and geometry of the compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation